Mussolini - Clark, Martin, 1938-2017 (Profiles In Power., 2014)
Benito Mussolini was a brilliant Socialist journalist who in 1914 declared war, put himself at the head if the anti-Socialist movement in Italy, manoeuvred himself into power by 1933 and ruled the country until overthrown in 1943. He was a dynamic but insecure personality, who appeared dictatorial but always had to share power with the military and bureaucratic establishment. Mussolini founded an Empire in Africa and tried to 'make Italians' in his own heroic, war like image, but in fact failed to even control his own family! In June 1940, when France fell, he could not resist joining in.